2013
DOI: 10.3928/01477447-20130523-08
|View full text |Cite
|
Sign up to set email alerts
|

Driving After Orthopedic Surgery

Abstract: As a result of reading this article, physicians should be able to: (1) Identify preoperative factors that may contribute to a patient's ability to return to driving after orthopedic surgery. (2) Understand the role of upper-extremity immobilization and how it may impair a patient's ability to operate a motor vehicle. (3) Recognize how various forms of lower-extremity immobilization (e.g., controlled ankle-motion boot, cast, and Aircast Walker) affect braking reaction times and total braking times. (4) Be aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Pain and limitation in motion or function of upper and lower extremities can substantially affect driving safety. Several reviews on this topic have been published [8,18,40,52], however in this study, we expanded on previously published reviews by performing a search in a systematic format, evaluating the quality of the studies, and including data from patient surveys. In addition, prior reviews focused primarily on one procedure or types of procedure, without compiling these data in a systematic format or recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain and limitation in motion or function of upper and lower extremities can substantially affect driving safety. Several reviews on this topic have been published [8,18,40,52], however in this study, we expanded on previously published reviews by performing a search in a systematic format, evaluating the quality of the studies, and including data from patient surveys. In addition, prior reviews focused primarily on one procedure or types of procedure, without compiling these data in a systematic format or recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Several review articles [8,18,40,52] have discussed the issue of driving after orthopaedic surgery and injuries. These articles discussed observer-reported outcome measures such as brake response time, brake force, and simulators that have been used to evaluate driving ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition time was the time of lower limb moved from the accelerator pedal to the brake pedal. In the past study, it concluded that there were many factors could affect the brake reaction time, such as age [12], gender [13], visual ability [14,15], task complexity [16,17], muscle force [18], and drug intake [19]. …”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 The decision to resume driving involves numerous factors. 4 Regardless of the multifactorial nature of the issue, medicolegal trends, including possible litigation, are commonly putting the responsibility for the decision solely on the patient. 1 5 6 Some authors have advocated that physicians should not give detailed advice about when a patient can resume driving.…”
Section: Introductionmentioning
confidence: 99%